Geneza i rozwój koncepcji wolności gospodarczej w ujęciu historyczno-prawnym - Mateusz Kowalewski (Studia Prawa Publicznego, 2022)
The aim of the article is to define the concept of economic freedom, using the ideas of the most important representatives of this doctrine. The article refers to the chronology and development of the concept of economic freedom, as well as the evolution of the policy of economic freedom along with the specification of the legal foundations determining the status of economic freedom over the centuries. The author refers only to the most important concepts for the issue in question, focusing on: (1) issues related to economic law and economic freedom or (2) aspects relevant to it in a given period. The initial thesis of the research is that economic freedom policy is a dynamic area, as evidenced by the multitude of legal acts implemented or amended every few years. Where specific legal phenomena are studied and need to be qualified at the same time, reference has been made primarily to the existing stock of well-known institutions. Economic freedom is a topic that has been the subject of lively discussion for many years. At its core, at various times, there were difficulties in determining (defining) economic freedom and its position in a given state. The political transformations lasting hundreds of years have caused economic changes in the state, accompanied by legal problems. The issue of economic freedom is related to the formation of relations between various entities operating on the territory of the state, and especially to how the state as an institution relates to entrepreneurs. Economic freedom has a significant impact on modern states, often leading to a change in their organizational model. For this reason, questions arise: What is economic freedom? What was its evolution? What is the attitude of the state to economic freedom? To what extent is economic freedom de facto “freedom” and what does it mean?